Neoliberalism and Inclusive Education: A Critical Ethnographic Case Study of Inclusive Education at an Urban Charter School - Mac, Sylvia (Critical Education, 2022)
At a time when the United States Department of Education openly advocates for neoliberal, free market policies, exploration of these efforts is needed. Investigation into one such effort, charter schools, can help provide insight into complicated questions surrounding the value and impact of these schools, especially on the marginalized populations they often serve. In this study, I explored how these neoliberal principles impacted the experiences of special education students at a small, urban charter school in Southern California. Three broad themes emerged from the data: 1) school size in the competitive education marketplace, 2) the illusion of choice and quality in a school of choice, and 3) the unrealized promise of inclusion in a neoliberal environment.  Implications of neoliberalism on the experiences of poor, disabled students are discussed. Future research directions include case studies and ethnographies situated at the intersection of special education, neoliberalism, and inclusion in the United States.